Advancements in Technology-Based Assessment and Intervention for Children with Developmental Disorders - Ghasemzadeh, Azizreza; kia kojori , Razie; Saadat , Maryam; Alizadeh , Zahra (KMAN Counseling & Psychology Nexus, 2023)
The letter explores the critical role of technology in enhancing developmental assessments and interventions for children. It emphasizes the importance of early intervention in mental well-being issues among children and adolescents, the necessity of empirical research in decision-making regarding child maltreatment, and the recognition of forensic odontology for identifying child abuse cases. The authors discuss the potential of technology-driven evaluations and interventions in addressing specific needs of children in low- and middle-income countries, highlighting the effectiveness of video modeling in improving social skills in children with ADHD and the significance of technology in enhancing parental practices and early childhood interventions. The paper also stresses the need for early, parent-focused, multi-channel interventions to support responsive caregiving and child development. It presents evidence on the positive impact of technology-based interventions in improving maternal mentalization capabilities, underscoring technology's role in promoting psychosocial well-being and supporting early child development. However, the article also acknowledges challenges such as managing child and adolescent mental health problems, the need for empirical research in child maltreatment decision-making, and enhancing awareness of forensic odontology among dental practitioners. In conclusion, the authors call for an integrated approach that includes technology-based solutions for a comprehensive support system for child development. They advocate for further research and development of technology-based interventions, emphasizing the importance of interdisciplinary approaches and the active role of practitioners in early learning to ensure optimal child development outcomes. Additionally, the article highlights the crucial role of policymakers in incorporating technology-based assessments and interventions into child development programs to foster holistic development in the African context and beyond.